Fabrication of poly(vinylidene fluoride) film and application to printing technology - Atsuki SHIRATORI (The Japan Society of Mechanical Engineers, 2016)
Poly(vinylidene fluoride) (PVDF) has four crystalline structures (α, β, γ and δ phase structures) in solid state. Only α-phase structure shows no crystal dipole, but this phase structure is converted easily into other phase structures according to some schemes. Generally, PVDF is given uniaxial stretch and polarization processes in order to convert into β-phase structure before sensor and actuator film use. However, we recently found a novel method in which PVDF film structure became β-phase without mechanical deformation processes. Furthermore, this technique enables us to apply printing technology, and realize the creation of free-form 3D sensor and actuators. No one can see free-form PVDF printer up to the present. The aim of the present study is to evaluate the crystalline structure and cross-sectional profile for PVDF films fabricated by present method. In addition, a novel PVDF printer, which can draw free-form 2D PVDF film, is developed on the basis of experimental results. First, a PVDF film is fabricated by dropping and drying a PVDF solution droplet. In this film fabrication, some PVDF solution droplets are prepared by changing the combination of the PVDF solution drop quantity and PVDF concentration in solution. Second, their PVDF crystalline structure is analyzed with an X-ray diffraction device. Then, PVDF film cross-sectional profile is measured with 3D shape measurement machine. In addition, the PVDF crystallinity degree is measured by differential scanning calorimetry. Third, a novel PVDF printer system is developed on the basis of present fabrication method. Then, the outline of free-draw 2D picture is printed as PVDF point drawing film on a 12mm×12mm glass plate, and the accuracy is investigated for printed PVDF films.